Pengaruh Customer Relationship Management Dan Kepuasan Terhadap Loyalitas Anggota - I Wayan Suartina; Anak Agung Ngurah Sadiartha; Ni Nyoman Rahayu Diantari Ady (Widya Manajemen, 2020)
The purpose of this study was to determine the effect of customer relationship management on member satisfaction, the effect of member satisfaction on member loyalty, the effect of customer relationship management on member loyalty, and the influence of customer relationship management on loyalty which is influenced by member satisfaction. This research was conducted at Village-Owned Enterprises (BUMDes) throughout Penebel District, Tabanan, Bali with a sample of 100 people who were determined using the Slovin method and the determination of the sample using incidental sampling. Testing instruments and analysis tools include validity test, reliability test, and path analysis accompanied by Sobell test. Based on the results of the path analysis test, it was found that customer relationship management has a positive and significant effect on member satisfaction, member satisfaction has a positive and significant effect on member loyalty, customer relationship management has a positive and significant effect on member loyalty and based on the results of the Sobell test, member satisfaction has been proven. mediating the relationship between the influence of customer relationship management on member loyalty is seen from the value of Z-score (4.84)> Z-table (1.66). Suggestions given in this study are BUMDes in Penebel District are suggested to further improve customer relationship management strategies to increase member satisfaction and loyalty from members.